Ureteral Obstruction in Endometriosis - Upadhyay, Amit Mani; Kunwar, Ashok; Shrestha, Sanjesh; Tiwari, Kabir; Pradhan, Hema Kumari; Dangal, Ganesh (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aim: Endometriosis is defined as functional endometrial glands and stroma that occur outside the uterine cavity. It is an estrogen dependent, benign, inflammatory disease that affects women during premenarcheal, reproductive and postmenopausal hormonal stages. Methods: This is a retrospective review of six cases with diagnosis of ureteral endometriosis. All the patients were referred to Department of Surgery, Kathmandu Model Hospital and the study period was from September 2015 to August 2018. Results: In our study all the patients had involvement of the ureter. All the patients who had undergone open surgery had extrinsic involvement of the ureter. Two patients who had mild distal ureteric stenosis only were managed by diagnostic URS and retrograde DJ stenting. Another two patients with right distal ureteric stenosis were managed initially with retrograde DJ stenting but after removal of ureteric stent and in subsequent follow up the degree of hydroureteronephrosis increased in both the cases. These two patients were finally undergone right Lich Gregoir ureteroneocystostomy. In the remaining two patients, ureterorenoscopy (URS) guided double J stenting were attempted but failed to insert the stent due to stenosed ureter so they underwent open abdominal hysterectomy with excision endometriotic cyst with ureterolysis and double J stenting. Conclusions: Ureteral endometriosis is a rare disease presenting most commonly with nonspecific symptoms and signs and thus making preoperative diagnosis often difficult for the clinicians. Treatment of ureteral endometriosis is primarily surgical. The surgical procedures which are usually performed are excision of all endometriosis lesion, ureterolysis, ureterectomy with ureteroureteral anastomosis and ureteroneocystomy.